The Future of Auditing in the Age of Automation: Leveraging Technology to Enhance Efficiency and Accuracy - Chairunnas, Arnadi; Hidayat, Muhammad (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research discusses the impact of the integration of new technologies such as artificial intelligence (AI), machine learning, and blockchain technology in modern audit practices. The aim is to explore how this technology improves audit efficiency and accuracy as well as the challenges faced in its adoption. The research method uses a systematic approach by collecting the latest literature from international databases using the PRISMA method. The research results show that the adoption of advanced technology in auditing results in improved audit quality, operational efficiency and better risk identification capabilities. Implications of this research include the importance of technical training for auditors, the need for better data security, and challenges related to the costs of implementing new technology in audit firms.